Perfil do idoso atendido na atenção primária à saúde e aspectos associados à satisfação com o atendimento - Medeiros, Kaio Keomma Aires Silva (2017)
The aim of this study was to describe the profile about the elderly in primary health care and the aspects associated with satisfaction with health care. An epidemiological, descriptive, cross-sectional and quantitative study was carried out in Campina Grande, in the state of Paraíba, Brazil, between 2016 and 2017. The sample consisted of 162 participants who were recruited by conglomerates, considering eligibility criteria. The data were collected from our own instrument and analyzed through descriptive statistics. The main results point to a predominance of women, a high age group, with reduced education and a low per capita income. Still, the relevant quantity referred to illness, mainly due to cardiovascular diseases. The level of satisfaction with primary health care was high, associated with obtaining medical care; having waited until an hour in the last contact; having the adequate communication with professionals; and being able to receive home visit. The reality that circumscribes the elderly connected with primary health care is permeated, on the one hand, by positive aspects, such as the high satisfaction with the medical care, the reduction of the number of hospitalizations and the reduction of waiting time in queue, and the adequate communication; and on the other hand, negative aspects, such as low participation in care programs and home visits, which should be considered for its expansion and consolidation to this population.